Supply chain management : some reflections to improve its influence in business Strategy - Arredondo, Carlos Raúl (2021)
Fil: Arredondo, Carlos Raúl. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina